Factors influencing psychotropic prescription by non-psychiatrist physicians in a nursing home for the elderly in Brazil - Stella, Florindo [UNESP]; Caetano, Dorgival [UNESP]; Pacheco, Jaime Lisandro [UNESP]; Sé, Elisandra Villela Gasparetto [UNESP]; Lacerda, Acioly Luiz Tavares [UNESP] (Associação Paulista de Medicina (APM), 2006)
CONTEXTO E OBJETIVO: Embora os psicotrópicos sejam uma das classes de medicações mais prescritas em abrigos para idosos, os estudos avaliando o seu padrão de prescrição são limitados em número e escopo. Este estudo visou investigar os fatores associados ao uso de psicofármacos em um abrigo para idosos no Brasil. TIPO DE ESTUDO E LOCAL: Estudo retrospectivo observacional realizado no Abrigo da Velhice de Rio Claro, Instituto de Biociências, Universidade Estadual Paulista. MÉTODOS: Dados sobre prescrições foram extraídos dos prontuários médicos dos 108 idosos moradores do abrigo. Sessenta e cinco sujeitos (idade média ± desvio padrão = 74,5 ± 9,4 anos), em uso regular de medicação, constituíram a amostra. Foram examinados os efeitos das variáveis sociodemográficas e clínicas sobre o padrão de prescrição de psicofármacos. RESULTADOS: As mulheres recebiam mais psicofármacos (p = 0.038); indivíduos em uso de medicações para doenças cardiovasculares recebiam menos psicofármacos (p = 0.001). Houve correlação negativa entre número de psicofármacos prescritos e, ambos, idade (p = 0.009) e número de medicações clínicas (p = 0.009). CONCLUSÃO: Embora preliminares, os resultados indicam as doenças cardiovasculares como a variável clínica que mais influenciou a prescrição de psicofármacos. Uma excessiva precaução por parte dos clínicos pode explicar parcialmente este resultado. Novas investigações, com amostras maiores e de diferentes regiões são desejáveis para confirmação destes dados.

CONTEXT and OBJECTIVE: Although psychotropics are one of the classes of medications most prescribed in nursing homes for the elderly, studies examining prescribing patterns are limited in both number and scope. The present study was undertaken to investigate factors associated with general psychotropic use in a nursing home in Brazil. DESIGN and SETTING: Retrospective observational study at the Nursing Home for the Elderly, Institute of Biosciences, Universidade Estadual Paulista. METHODS: Information on prescriptions was retrieved from the medical records of 108 elderly residents in a nursing home. Sixty-five of these patients, with mean age 74.5 years (± standard deviation 9.4 years), who were taking medications on a regular basis, comprised the sample. The effects of demographic and clinical variables on the psychotropic prescription pattern were examined. RESULTS: Females were more likely to receive psychotropics (p = 0.038). Individuals on medicines for cardiovascular diseases received psychotropics less frequently (p = 0.001). The number of prescribed psychotropics correlated negatively with both age (p = 0.009) and number of non-psychotropic drugs (p = 0.009). CONCLUSIONS: Although preliminary, the present results indicated that cardiovascular disease was the clinical variable that most influenced psychotropic prescription. Physicians' overconcern regarding drug interactions might at least partially explain this result. Further investigations involving larger sample sizes from different regions are warranted to confirm these findings.
Fatores que influenciam a prescrição de psicofármacos por médicos não-psiquiatras em um abrigo de idosos no Brasil
Keywords: Envelhecimento; Asilos para idosos; Prescrição de medicamentos; Cardiopatias; Psicofarmacologia; Aging; Homes for the aged; Drug prescriptions; Heart diseases; Psychopharmacology